Effectiveness of Kangaroo Mother Care in enhancing survival and health outcomes among preterm neonates in a resource-limited tertiary care setting - Rubina Akhtar; Rukhsana Karim; Syeda Sitwat Fatima; Sabah Safdar (Khyber Medical University Journal)
Objective: To evaluate the efficacy of Kangaroo Mother Care (KMC) in improving survival rates, weight gain, and reducing hospital stay duration among preterm neonates in a tertiary care hospital in Pakistan.